Response to The Growth And Production of Two lowland Maize Varieties (Zea mays L.) to Organic Fertilizer - Rahmi Ami; Diana Sofia Hanafiah; Rosmayati Rosmayati (Jurnal Agroekoteknologi, 2016)
This study aims to determine the growth and production responses of two lowland maize varieties to organic fertilizer. This study was held in the screen house, faculty of agriculture, University of North Sumatera, from January 2014 until May 2014. This research using randomized block design with 2 factors, factor 1: maize varieties (V): V1 (Pioner 12), V2 (Bisma), and factor 2 with 4 levels, namely P0: no manure (control), P1: 10 g of cow manure / plant, P2: 23 ml of liquid manure (cow urina) / plant, P3: 10 g of cow manure fertilizer +23 ml liquid manure / plant. The result from of this research was not significantly on parameters plant height the number, of leaves and the age of flowering. Interaction of organic fertilizer gave significantly effect to varieties treatment. The high heritability value was showed by parameters the number of leaves,the age of male flowering and the age of female flowering.Keywords: organic fertilizer, corn, varieties